Comparative Study of Control Strategies for Under Actuated Manipulator - Abed, Joudeh Yasin (2006)
A Master of Science Thesis in Mechatronics Submitted by Joudeh Yasin Abed Entitled, "Comparative Study of Control Strategies for Under Actuated Manipulator," June 2006. Available are both Soft and Hard Copies of the Thesis.